Respiratory health in athletes: facing the COVID-19 challenge with Dr James Hull - Hull, J. (BMJ talk medicine, 2020)
In this cutting-edge podcast with Dr James Hull - a leading authority on respiratory health in athletes - we discuss the challenges facing athletes and healthcare professionals following infection with the novel coronavirus. We cover a few case-studies, and practical points for all SEM professionals to consider.